A Suggested Vision for Conducting of Electronic Supervision in the General Directorate of Education, Dhi Qar Governorate - Zuhair Nadhem Khayoon Algabry1 , Ali Abdul Hussein Ali Al-Farjawi 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The tremendous scientific and technological progress in various fields of knowledge is one of the mostimportant features of the era in which we live in its present and future, as the progress of this era requirespreparing a generation capable of dealing with this progress and changes in the modern technologies as wellas the rapid flow of information have left clear implications for education. That the information technology,such as computers, the Internet and the attached multimedia, are among the most successful means ofproviding a rich learning environment, as for teachers, by contacting to the global network enables theteacher to access educational and general experiences that are difficult to access in other ways. So theimportance of the Internet lies in its ability to connect among people across enormous distances and betweendifferent information sources. The use of this technology increases educational opportunities, extendingthem to more than the range of departments, as this is known as the e-learning that distinguishes the schoolof the future.